KKN Management Center and Region Development Research Institutions and Community Devotion State University of Yogyakarta - Rafika, Ageng Setiani; Faridah, Ida; Sangaji, Aziz Andrean (Pandawan, 2017)
(KKN) is held in Kradenan Hamlet, Srimulyo Village, Piyungan Sub-district, Bantul District, Special Province of Yogyakarta, Real Working Lecture (KKN), Kradenan Hamlet consists of 4 RT. The population of approximately 173 families. The inhabitants of Kradenan are all Muslims, and the majority live as factory workers. The purpose of KKN is in Kradenan Hamlet, to explore, to develop the potential of the Kradenan Hamlet community, and to advance the thinking of the people of Kradenan Hamlet. The Real Work Lecture Program has been implemented in the Kradenan Hamlet pre-trial training and screening of Java-uploaded films. The purpose of the pre-trial training is to explore and develop the potential of Kradenan Hamlet people, and the purpose of holding Javanese uploading films is to give awareness since the early importance of paying attention and doing the uploads to anyone and anywhere. Children are able to understand the pranatacara technique properly and correctly. Children have also started to get used to being in line with the uploads to anyone and wherever they are. Programs held in the right sense are held in Kradenan Hamlet. One of the programs that are in line with the Hamur Hamada people's desires are pre-training training and targeted to adolescents, young people who aim to have the next generation and can open the insight to the community in seeking additional side work. Keywords: KKN, Bantul Regency, Kradenan Village, Srimulyo Village, Piyungan Sub-district, Pranatanacara Training.